2020
DOI: 10.3389/fsufs.2019.00120
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Dryland Crop Management to Regional Climate via Simulation. Part I: U.S. Southern High Plains Cotton Production

Abstract: Over semi-arid agricultural regions such as the U.S. Southern High Plains (SHP) producers of dryland crops need to know which management practices increase yields and decrease production risk. Here, a modeling approach is used to explore management options (MO) that increase dryland cotton yields and estimate those practice's yield risk effects under current SHP climate conditions. To simulate current dryland yield variability, dense distributions of lint yield outcomes were generated using the CROPGRO-Cotton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…While the majority of cotton producers in the survey respondents rely on furrow or sprinkler irrigation, many are using or examining the potential for drip irrigation to reduce water quantities and energy costs. Dry land production, where cotton is grown without the aid of irrigation, has also been gaining popularity (Mauget et al, 2020). Biologically-based soil-building practices, such as crop rotation, cover crops and compost applications, have also been shown to increase the water-holding capacity of soils (Cambardella et al, 2015) and can lead to lessen applications of water over the growing season.…”
Section: Environmental Impacts Of Organic Management Techniquesmentioning
confidence: 99%
“…While the majority of cotton producers in the survey respondents rely on furrow or sprinkler irrigation, many are using or examining the potential for drip irrigation to reduce water quantities and energy costs. Dry land production, where cotton is grown without the aid of irrigation, has also been gaining popularity (Mauget et al, 2020). Biologically-based soil-building practices, such as crop rotation, cover crops and compost applications, have also been shown to increase the water-holding capacity of soils (Cambardella et al, 2015) and can lead to lessen applications of water over the growing season.…”
Section: Environmental Impacts Of Organic Management Techniquesmentioning
confidence: 99%
“…Dry land is a stretch of land that is never flooded or flooded during a large period of time in a year. From a geographical point of view, dry land is usually in the form of hilly soil with a wavy morphology, also has soil types that are poor in nutrients (Mauget, et al, 2020). In terms of rain availability, dry land also has a relatively low level of rainfall with short wet months.…”
Section: Introductionmentioning
confidence: 99%
“…In a preceding companion paper (Mauget et al, 2019; hereafter M19) a modeling-based method was demonstrated that identified climate-optimal practices in SHP dryland cotton production. Here, this approach is applied to dryland sorghum production.…”
Section: Introductionmentioning
confidence: 99%